Students’ Perception towards Synchronous and Asynchronous Learning Modes at Faculty of Teacher Training and Education (Equilibrium: Jurnal Pendidikan, 2023)
This study aimed to find out students' perceptions of synchronous and asynchronous learning modes. This research was conducted at the Faculty of Teacher Training and Education at Universitas Muhammadiyah Sumatra Utara. This study used a qualitative descriptive method and used random sampling. The subjects of this study were 50 students filling out the questionnaire and 8 students being interviewed. From the results of the study, it can be seen that as many as 72% of students are satisfied with the synchronous learning mode, and as many as 66% of students are satisfied with the asynchronous learning mode. It can be seen that more students like synchronous learning mode than asynchronous learning mode by online learning using whatssapp, google classroom, and zoom application.
Keywords: Online learning; Synchronous Learning; Asynchronous